Assessment of Aerosol Radiative Impact over Oceanic Regions Adjacent to Indian Subcontinent Using Multisatellite Analysis - S. K. Satheesh; V. Vinoj; K. Krishnamoorthy (Advances in Meteorology)
Using data from Ozone Monitoring Instrument (OMI) and Moderate Resolution Imaging Spectroradiometer (MODIS) instruments, we have retrieved regional distribution of aerosol column single scattering albedo (parameter indicative of the relative dominance of aerosol absorption and scattering effects), a most important, but least understood aerosol property in assessing its climate impact. Consequently we provide improved assessment of short wave aerosol radiative forcing (ARF) (on both regional and seasonal scales) estimates over this region. Large gradients in north-south ARF were observed as a consequence of gradients in single scattering albedo as well as aerosol optical depth. The highest ARF (−37 W m−2 at the surface) was observed over the northern Arabian Sea during June to August period (JJA). In general, ARF was higher over northern Bay of Bengal (NBoB) during winter and premonsoon period, whereas the ARF was higher over northern Arabian Sea (NAS) during the monsoon and postmonsoon period. The largest forcing observed over NAS during JJA is the consequence of large amounts of desert dust transported from the west Asian dust sources. High as well as seasonally invariant aerosol single scattering albedos (~0.98) were observed over the southern Indian Ocean region far from continents. The ARF estimates based on direct measurements made at a remote island location, Minicoy (8.3∘N, 73∘E) in the southern Arabian Sea are in good agreement with the estimates made following multisatellite analysis.